2022
DOI: 10.2147/idr.s376763
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Drug Resistance, and Risk Factors for Mortality Among Hematopoietic Stem Cell Transplantation Recipients with Hospital-Acquired Klebsiella pneumoniae Infections: A Single-Center Retrospective Study from China

Abstract: Objective Infection is the most common complication and cause of death after hematopoietic stem cell transplantation (HSCT). Our study aims to investigate the clinical characteristics and risk factors for death of Klebsiella pneumoniae infections in HSCT recipients, so as to provide evidence for guiding antibiotic use and improving prognosis in the future. Methods The epidemiology, clinical manifestations and drug resistance rate with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Further multivariate analysis revealed that the interval from diagnosis to transplantation > 180 days, septic shock, low platelet count and high bilirubin level at the initial stage of infection were independent risk factors for death. In previous reports, we have described the adverse effects of extended transplant interval: persistent disease state, multiple chemotherapy treatments, low immunity, poor body function, delayed donor cells implantation, etc (Liu et al, 2022). This is why both domestic and international guidelines unanimously recommend early transplantation for eligible patients (Blackburn et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further multivariate analysis revealed that the interval from diagnosis to transplantation > 180 days, septic shock, low platelet count and high bilirubin level at the initial stage of infection were independent risk factors for death. In previous reports, we have described the adverse effects of extended transplant interval: persistent disease state, multiple chemotherapy treatments, low immunity, poor body function, delayed donor cells implantation, etc (Liu et al, 2022). This is why both domestic and international guidelines unanimously recommend early transplantation for eligible patients (Blackburn et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial infection was defined as the occurrence of inflammatory reaction symptoms in the patient and the isolation of pathogenic microorganisms from blood or other normally sterile sites and exclusion of contamination and colonization (Horan et al, 2018). Infections occurred 48 hours after admission were considered hospital-acquired (Liu et al, 2022). Inappropriate empiric antimicrobial therapy was defined as the absence of microbial-sensitive antibiotics within 48 hours of specimen acquisition (Wan et al, 2017).…”
Section: Definitionsmentioning
confidence: 99%
“…In previous reports, we have repeatedly emphasized the disadvantages of prolonged transplantation interval: disease recurrence, repeated chemotherapy, bone marrow suppression, immunosuppression, mucosal damage, impaired organ function, excessive psychological pressure, delayed donor cell implantation, etc. ( Liu et al., 2022 ; Jia et al., 2023 ). Kikuchi M et al.…”
Section: Discussionmentioning
confidence: 99%